2018
DOI: 10.1155/2018/1321862
|View full text |Cite
|
Sign up to set email alerts
|

EIT Imaging of Intracranial Hemorrhage in Rabbit Models Is Influenced by the Intactness of Cranium

Abstract: Electrical impedance tomography (EIT) has been shown to be a promising, bedside imaging method to monitor the progression of intracranial hemorrhage (ICH). However, the observed impedance changes within brain related to ICH differed among groups, and we hypothesized that the cranium intactness (open or closed) may be the one of potential reasons leading to the difference. Therefore, the aim of this study was to investigate this effect of open or closed cranium on impedance changes within brain in the rabbit IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…Such a small blood infiltration in the surrounding healthy parenchyma could make the MRR clustering unable to distinguish the boundary real hemorrhage-healthy tissues that instead appears evident from the histopathology after the brain fixation. This hypothesis related to heparinization is supported by the work of Dai et al (2018), where authors, contrary to what has been herein described, used autologous nonheparinized blood into cerebral parenchyma for their experiment and observed in their results a clear distinction between hemorrhagic tissue and parenchyma [42].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Such a small blood infiltration in the surrounding healthy parenchyma could make the MRR clustering unable to distinguish the boundary real hemorrhage-healthy tissues that instead appears evident from the histopathology after the brain fixation. This hypothesis related to heparinization is supported by the work of Dai et al (2018), where authors, contrary to what has been herein described, used autologous nonheparinized blood into cerebral parenchyma for their experiment and observed in their results a clear distinction between hemorrhagic tissue and parenchyma [42].…”
Section: Discussionsupporting
confidence: 61%
“…As far as it strictly concerns the histopathology findings, in acute human spontaneous intracerebral hemorrhages, as well as in those induced by injecting blood in different animal models (42), primary tissue damage is followed by secondary pathological lesions, in which cellular and neuroinflammatory changes are poorly defined. Most of the studies published on this topic refer to 24/48 hours postmortem histological changes [43,44], especially focusing on the time and mass effect of the lesion, cerebral edema, and ischemic cell changes affecting the adjacent neural tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This phantom provides a standardized, efficient, and reproducible method for the construction of a head phantom for EIT that could be easily adapted to other fields in brain function research, such as transcranial direct current stimulation and EEG [120]. The FMMU group also confirmed that cranium completeness (open or closed) affects impedance changes within the brain when using EIT to monitor ICH [88]. Hence, cranium completeness should be considered when establishing an ICH model and analyzing the corresponding EIT results.…”
Section: Modeling Accuracymentioning
confidence: 93%
“…Most patients with ICH require a craniotomy. Dai and colleagues [88] investigated the effects of an open or closed cranium on impedance changes in the brain in a rabbit ICH model and reported that cranium completeness (open or closed) influenced impedance changes within the brain when using EIT to monitor ICH. Therefore, cranium completeness should be considered in future studies when applying EIT to monitor cerebral hemorrhage.…”
Section: Strokementioning
confidence: 99%
“…EIT is often used in the treatment of some lung failure diseases (Frerichs and Zhao, 2019). In addition to the application in lung diseases, there are also some clinical applications in tumor detection or early detection of some diseases for EIT (Ma et al, 2014;Dai et al, 2018;Lee et al, 2020;Yang et al, 2020). With the continuous development of EIT theory and technology, the clinical application of EIT technology will be more and more.…”
Section: Neonatal Pulmonary Function Imagingmentioning
confidence: 99%